Exploring Mobile Game Interactions - Pitsanu Chaichitwanidchakol; Witcha Feungchan (International Journal of Electrical and Computer Engineering (IJECE), 2018)
The mobile game industry has been growing rapidly in both the number of games and revenues. Choosing the right interactions for a game has become a major challenge for developers. Some developers use inappropriate interactions in their games which causes them to be less fun than they should be. This research focuses on gathering and defining possible mobile game interactions so as to guide and enable designers and developers to choose the right interactions for their games. The researchers have extensively reviewed and explored various mobile game interactions both through research studies and through existing mobile games. Subsequent to observations, mobile game interactions were then categorized as follows: 1) Touch interaction 2) Motion/Movement interaction 3) Video interaction 4) Sound interaction 5) Special purpose interaction 6) Location interaction 7) Electroencep-halography (EEG) interaction 8) Date/Time interaction 9) Weather interaction 10) Light interaction 11) Proximity interaction 12) Network interaction 13) Social interaction and 14) Bioinformatics interaction. These 14 interactions can be used to support gameplay, ideas, and innovation of mobile games.